New impulses from Europe's south: Spain and Portugal regrasp the initiative in the process of European integration - Günther Maihold; Andreas Maurer (Stiftung Wissenschaft und Politik (SWP), 2005)
At the end of February 2005, nearly twenty years after their accession to the then European Community, Spain and Portugal have once again given a clear signal of their identification with the European Union (EU): In Spain the first national referendum on the ratification of the Treaty establishing a Constitution for Europe (TCE) ended in a positive result, with 76.7% in favour; albeit that the low turnout clearly indicates the limits of this enthusiasm. In Portugal, a new government with a stable majority was elected. Prime Minister José Sócrates is keen to take on a central role in the process of European integration. A decisive factor in the future success of their efforts will be the question of whether Spain and Portugal are ready - beyond their shared interest in maintaining the inflow of money from the Structural and Cohesion Funds - to take on the political costs arising from their newly sworn European identity. (SWP comments /SWP)
Keywords: 320